2004
DOI: 10.1128/aac.48.9.3419-3424.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ertapenem Protein Binding on Killing of Bacteria

Abstract: The effect of protein binding on the antimicrobial activity of ertapenem was evaluated using the bacterial kill rate and concentration-response studies. Various proportions of human serum were utilized to determine the total and free-drug concentrations using a validated high-performance liquid chromatography assay. The MICs and kill curves were determined for test isolates of Enterobacter cloacae and Staphylococcus aureus at various percentages of human serum. The killing of bacteria was analyzed in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…However, these drug concentrations are sometimes presented as total drug concentrations while only the free drug is pharmacologically active (18,25). Also, free drug concentrations at the site of action/infection are much more relevant in determining efficacy (15,24), and exploring the concentration at the site of action has been recommended by regulatory agencies (1,2,8).…”
mentioning
confidence: 99%
“…However, these drug concentrations are sometimes presented as total drug concentrations while only the free drug is pharmacologically active (18,25). Also, free drug concentrations at the site of action/infection are much more relevant in determining efficacy (15,24), and exploring the concentration at the site of action has been recommended by regulatory agencies (1,2,8).…”
mentioning
confidence: 99%
“…It has been suggested that this is sometimes the case for ertapenem. Unbound (free) ertapenem concentrations are best associated with antimicrobial activity, and animal models have suggested that maintaining carbapenem concentrations above an organism's MIC for at least 40% of the dosing interval (Ն40% T Ͼ MIC) maximizes bactericidal effect (14,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, human serum on the one hand is less optimal for bacterial growth than microbiological standard media and on the other hand contains substances that possess antibacterial activity. Growth rates of Staphylococcus aureus, for instance, have been shown to be reduced in media containing human serum (61). Furthermore, when bacterial strains are exposed to antibiotics in active serum, even subinhibitory antibiotic concentrations can exert a bactericidal effect due to the synergistic effect of antibiotics and serum on bacterial growth (7,57,59).…”
Section: Protein Binding In In Vitro Studies Of Antimicrobial Activitymentioning
confidence: 99%
“…Furthermore, when bacterial strains are exposed to antibiotics in active serum, even subinhibitory antibiotic concentrations can exert a bactericidal effect due to the synergistic effect of antibiotics and serum on bacterial growth (7,57,59). There have been attempts to acclimate test strains to growth in human serum (61). Indeed, during these experiments, the tested organisms adapted to conditions in serum, despite the presence of antibacterial molecules.…”
Section: Protein Binding In In Vitro Studies Of Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation